Portal application of human unrestricted somatic stem cells to support hepatic regeneration after portal embolization and tumor surgery - Ghodsizad, Ali; Liedtke, Stefanie; Mehrabi, Arianeb; Karck, Matthias; Ruhparwar, Arjang (ASAIO journal, 2012)
Insufficient liver remnant volume still precludes patients with potentially resectable tumors from curative surgery. Clinically, it has been demonstrated that transplanted adult stem cells promote liver regeneration. However, the mechanisms of the observed functional improvements are unknown. The aim of our study was to evaluate the impact of transplanted human multipotent cord blood-derived unrestricted somatic stem cells (USSC) on liver regeneration and identify the underlying mechanisms in an ovine model. We performed partial embolization of the right liver lobe and grafted USSC in the portal venous system of the left liver lobe. After 4 weeks, livers were explanted and analyzed for differentiation of USSC into hepatocytes by histopathologic examination and for fusion of USSC with recipient hepatocytes by single-cell polymerase chain reaction. The studies revealed that transplanted USSC differentiate into hepatocytes and produce human albumin. No ovine DNA was found in the hepatocytes with a human phenotype. Transplantation of USSC enhances the number of viable hepatocytes in liver disease by differentiation and opens new therapeutic perspectives.